2022
DOI: 10.1097/j.pain.0000000000002694
|View full text |Cite
|
Sign up to set email alerts
|

Altered serum bile acid profile in fibromyalgia is associated with specific gut microbiome changes and symptom severity

Abstract: Supplemental Digital Content is Available in the Text.Women with fibromyalgia show significant alterations in serum bile acids and gut bile-metabolizing bacteria. These alterations are correlated with syndrome symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…6). Moreover, we found alterations in secondary bile acid metabolism (decreased ursocholate in plasma and increased lithocholic acid sulphate in the feces), consistent with previous findings in fibromyalgia 4 .…”
Section: Pervasive Changes In Mice Colonized With Fibromyalgia Microb...supporting
confidence: 92%
See 1 more Smart Citation
“…6). Moreover, we found alterations in secondary bile acid metabolism (decreased ursocholate in plasma and increased lithocholic acid sulphate in the feces), consistent with previous findings in fibromyalgia 4 .…”
Section: Pervasive Changes In Mice Colonized With Fibromyalgia Microb...supporting
confidence: 92%
“…1c). Fibromyalgia is more prevalent in females, and gut microbiota composition in fibromyalgia has only been studied in women [2][3][4] ; therefore, the weekly FMTs were performed by transplanting human stool from women with fibromyalgia and age-matched healthy controls into germ-free female mice (Fig. 1a).…”
mentioning
confidence: 99%
“…One study compared the microbiome in 77 women with fibromyalgia and 79 controls using 16S rRNA gene amplification and whole-genome sequencing. Significant differences were revealed in the rate of bacterial taxa 29 . Anti-inflammatory Faecalibacterium and Bifidobacterium species and other species that produce the antiinflammatory compound butyrate are decreased in number.…”
Section: Gut Microbiotamentioning
confidence: 97%
“…Hierarchical clustering was used in another study to evaluate chronic pain subgroups [ 80 ]. In addition, researchers found that ML could diagnose fibromyalgia with nearly 90% accuracy using a composition of the microbiome [ 81 ]. Nearly 20 bacterial species were identified to increase or decrease among patients with fibromyalgia.…”
Section: Use-case Examplesmentioning
confidence: 99%